El dibujo infantil y su relación con las habilidades y destrezas del aprendizaje emocional en los niños/as de 5 años de la I.E N°288 Ana Sofía Guillena Arana - Roque Grandez, Milagros (2014)
The Children 1 as drawings by is able to express their psychological state and emotional wel~-being (say what you feel), is also a means of so'?ializing with others and it enables them to make connection between his inner world and outer world. The overall objective of this research was to determine the relationship between child drawing skills and emotionallearning abilities in children 1 as 5 years of El No. 288 "Ana Sofía Arana Guildford" Rioja district The research design was basic - descriptiva correlationaJ: The sample consisted of 19 children (07 boys and 12 girls). The experiment was carried out for two months with the implementation of children's drawing Test, to assess the scribble, HouseTree- Person and The Human Figure and systematic observation of children 1 as the study group to assess the abilities skills and abilities of emotional learning in individual, achieving accepting our research hypothesis, as the correlation coefficient of Pearson, a calculated value de rs = O, 7087 greater than the tabulated value de r a = ±0,456 right to give a direct positive relationship between child drawing with the abilities and emotional learning abilities in children 5 years of lnitial Educational lnstitution district No. 288 Rioja.